Statistical issues of hazardous agents - Wolfgang Urfer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2001)
Evaluation of hazards associated with exposure to chemicals, understanding of relationships between dose and adverse effect, extrapolation of effects from high experimental doses to low doses associated with actual exposures, and extrapolation from effects observed in animals to effects expected in humans are the main issues of statistical research in risk assessment of hazardous agents. We discuss statistical aspects of inhalation toxicology, proof of hazard, genetic toxicology and the role of oncogenes in carcinogenesis. Finally, we outline the need for more statistical research to identify hazardous agents by DNA and protein sequence analysis.
Keywords: 519